Cytoskeletal and Cytoskeleton-Associated Proteins: Key Regulators of Cancer Stem Cell Properties - Yuqiang Li; Dan Wang; Heming Ge; Cenap Güngör; Xuejun Gong; Yongheng Chen (MDPI AG, 2022)
Cancer stem cells (CSCs) are a subpopulation of cancer cells possessing stemness characteristics that are closely associated with tumor proliferation, recurrence and resistance to therapy. Recent studies have shown that different cytoskeletal components and remodeling processes have a profound impact on the behavior of CSCs. In this review, we outline the different cytoskeletal components regulating the properties of CSCs and discuss current and ongoing therapeutic strategies targeting the cytoskeleton. Given the many challenges currently faced in targeted cancer therapy, a deeper comprehension of the molecular events involved in the interaction of the cytoskeleton and CSCs will help us identify more effective therapeutic strategies to eliminate CSCs and ultimately improve patient survival.